2022
DOI: 10.1155/2022/3979203
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress-Related Semen Quality and Fertility in the Male Arabian Yellowfin Sea Bream (Acanthopagrus arabicus) Fed a Selenium Nanoparticle-Supplemented Plant Protein-Rich Diet

Abstract: A three-month research was conducted to evaluate the influence of supplementing a plant protein- (PP-) rich diet (60% of fish meal (FM) was replaced with a mixture of alternative PP sources) with selenium nanoparticles (Se-N) on sperm kinetics, fertilization capacity, and antioxidative responses in Arabian yellowfin sea bream (Acanthopagrus arabicus) males. In this point, graded levels of Se-N at 0, 0.5, 1, 2, and 4 mg/kg were added to the PP-rich diet. Also, a FM-based diet was used as a positive control. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 99 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…Selenomethionine, as the central part of organic Se, is retained as selenoprotein and plays a role in protein synthesis and cellular growth [ 6 , 53 ]. In addition, Se is an integral part of the deiodinase enzyme that bioconverts thyroxin to triiodothyronine and profoundly affects the synthesis and release of growth hormones [ 2 ]. Moreover, Se, as the central part of GPx, provides high antioxidant capacity and protects cell membranes against reactive oxygen species and consequently can improve growth rate in farmed aquatic species [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selenomethionine, as the central part of organic Se, is retained as selenoprotein and plays a role in protein synthesis and cellular growth [ 6 , 53 ]. In addition, Se is an integral part of the deiodinase enzyme that bioconverts thyroxin to triiodothyronine and profoundly affects the synthesis and release of growth hormones [ 2 ]. Moreover, Se, as the central part of GPx, provides high antioxidant capacity and protects cell membranes against reactive oxygen species and consequently can improve growth rate in farmed aquatic species [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A basal diet was supplemented with five levels of SeNP, including 0 (Control), 0.5 mg kg −1 (SeNP0.5), 1 mg kg −1 (SeNP1), 2 mg kg −1 (SeNP2), and 4 mg kg −1 (SeNP4) ( Table 1 ) according to Khademzadeh et al [ 2 ]. The selected dosages of the SeNP were based on previous studies in other fish species and Asian sea bass [ 8 , 9 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Working on the same species, Khademzade et al. [66] demonstrated that including nano-Se at 2–4 mg/Kg in plant-protein diets improved sperm kinetics and enhanced fertility potential in male broodfish. These results indicate that nano-Se is an efficient source of Se for improving the reproductive performance in male and female broodfish.…”
Section: The Status Of Nano-se Supplementation In Aquafeedsmentioning
confidence: 99%
“…Similar results have been reported in common carp and crucian carp, with optimal addition concentrations of 0.7 and 0.5 mg/kg, respectively ( Saffari et al, 2017 , Zhou et al, 2009 ). Furthermore, SeNPs improve sperm motility and exhibit an antagonistic effect against heavy metals in fish ( Khademzade et al, 2022 , Saad et al, 2022 , Yin et al, 2021 ). Therefore, this study aims to select the most suitable selenium feed additives for fish from SeNPs, selenite, and SeMet.…”
Section: Introductionmentioning
confidence: 99%